Optimalisasi Kemanfaatan Riset Hukum bagi Upaya Peningkatan Kesadaran Hukum Masyarakat yang Berkesejahteraan - Handoyo Prasetyo; Bambang Waluyo; Binsar Jon Vic S; Subakdi Subakdi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Doctoral legal research often gets trapped in academic formality and lacks practical benefit for the public. This Community Service (PKM) activity aims to optimize the utility of legal research through educational dissemination on the axiology of philosophy of science and the enhancement of practical legal awareness among residents of Cilempuk Hamlet, Purwamekar Village, Karawang Regency. The implementation method employed a participatory educational approach comprising socialization, interactive presentation on the Trias Philosophy of Science (ontology, epistemology, and axiology as the crown of a dissertation), and an open legal discussion. The results indicated an increased public understanding regarding the significance of axiological value ("so what?") in law and legal research. Residents demonstrated an understanding of legal pluralism (written laws and unwritten/customary laws), internalized daily legal compliance such as traffic discipline and mutual respect, and strengthened national commitment rooted in religious values. This activity successfully transformed theoretical-philosophical concepts into practical legal awareness at the rural level to foster a prosperous community.